Pemodelan Basis Data Penyewaan Motor Listrik Menggunakan ERD, CDM, dan PDM - Rafael Christian Pramuditya; Kenny Tanna Haholongan Pandia; Hafiz Muhammad Shahzaib; Zatin Niqotaini (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2026)
The development of digital-based transportation technology demands a fast, accurate, and environmentally friendly data management system, particularly in electric motorcycle rental services. However, the complexity of managing operational data regarding fleets, battery conditions, and payment transactions often triggers risks of data redundancy and slow application performance if not supported by a robust database structure. This study aims to design a structured and efficient database architecture for the Electric Motorcycle Rental Information System. The research method was carried out progressively through data modeling phases, including Entity Relationship Diagram (ERD), Conceptual Data Model (CDM), and Physical Data Model (PDM). The results successfully mapped five core system entities: Pelanggan (Customer), Motor_Listrik (Electric Motorcycle), Stasiun (Station), Penyewaan (Rental), and Pembayaran (Payment), which are fully integrated through One-to-Many and One-to-One cardinality rules. The transformation from CDM to PDM generated a production-ready physical database blueprint with specific data types and proper implementation of Primary Key and Foreign Key mechanisms. In conclusion, this database design successfully creates a ready-to-use physical database schema capable of maintaining data integrity and preventing data redundancy to support efficient rental system operations.